العمليات الذهنية المصاحبة لفهم النص القرآني لدى طلاب المرحلة الثانوية : دراسة تشخيصية علاجية - العتيبي، نايف بن عضيب بن فالح العصيمي (جامعة الملك سعود - الجمعية السعودية للعلوم التربوية والنفسية, 2016)
استهدفت الدراسة تشخيص العمليات الذهنية المصاحبة لفهم النص القرآني لدى طلاب المرحلة الثانوية وعلاجها لدى هؤلاء الطلاب؛ ولتحقيق الهدف السابق أعد الباحث قائمة بالعمليات الذهنية المصاحبة لمهارات فهم النص القرآني لدى طلاب الصف الأول الثانوي، وتم بناء اختبار لقياس هذه العمليات تكون من عشرين سؤالاً، وطبق على عينة من الطلاب بلغ عددهم" 112" طالبا، وقد أظهرت نتائج الدراسة ضعف ممارسة طلاب الصف الأول الثانوي للعمليات الذهنية المصاحبة لفهم النص القرآني ،إذ بلغ مستوى تمكن الطلاب من هذه العمليات ككل نسبة مقدارها "52.65 %"،وهو مستوى متدنٍ للغاية مقارنة بمستوى التمكن المحدد في الدراسة الحالية وهو نسبة "80 %"، كما كشفت نتائج الدراسة عن ضعف ممارسة الطلاب للعمليات الذهنية الفرعية المصاحبة لفهم النص القرآني، وقد كانت عملية معرفة البنية التركيبية للنص القرآني أقل العمليات الفرعية بنسبة تقدر بـ "47.32 %"، في حين جاءت عملية التنظيم الذاتي لفهم النص القرآني في المستوى الثاني بنسبة" 54%"، وكانت أعلى العمليات هي عملية الضبط والتحكم ،إذ بلغت نسبتها" 55%"، بيد أن جميع العمليات الذهنية الفرعية، لم تبلغ حد التمكن، كما تفاوت ترتيب العمليات الذهنية الفرعية المصاحبة لفهم النص القرآني، فاحتلت عملية الحكم على دقة فهم النص القرآني الترتيب الأول بين هذه العمليات بمتوسط قدره "1.33"، وبانحراف معياري "0.80"، في حين جاءت عملية معرفة الطرائق المختلفة لفهم النص في الترتيب الأخير بمتوسط بلغ "0.75"، وبانحراف معياري "0.87"، ثم قام الباحث ببناء تصور مقترح لتنمية هذه العمليات، وقد أوصت الدراسة ببعض التوصيات منها: ضرورة تضمين العمليات الذهنية المصاحبة لفهم النص القرآني في منهج التفسير لطلاب الصف الأول الثانوي، وتزويد المنهج بأدوات قياس حديثة تكشف عن العمليات الذهنية المصاحبة لفهم النص القرآني، وتدريب المعلمين على الاستراتيجيات التعلمية الحديثة لتنمية العمليات الذهنية المصاحبة للفهم.
The study aimed to diagnose mental processes associated with the understanding of the Quranic text for secondary school students and treated with these students ; To achieve the former goal , the researcher prepared a list associated with mental processes associated with skills to understand the Quranic text of the first year. I have been building a test to measure these processes are twenty questions which was applied to sample of students numbered (112) students , have the results of the study showed the weakness of the practice first grade secondary students to mental processes associated with the understanding of the Quranic text . The results showed the weakness of the practice of first-grade students of secondary operations associated with the mental understanding of the Quranic text, reaching the level enables students to these operations as a whole of (52.65%) rate , A level too low compared to the level of being able to set in the present study , a ratio of (80%), also revealed the results of the study on the weak students practice operations Sub operations associated with the Quranic text , was the knowledge of the structure composition Quranic text below sub-processes by an estimated (47.32%) process , while self-regulated learning processes came to metacognitive reading comprehension the Quranic text in the second level by (54 %), the highest of operations is the setting and control process , which accounted for (55%) , however, that all processes subsidiary , did not amount to being able , as varied order of operations mental Sub associated with metacognitive reading comprehension Quranic text , Ranking the process of judging the accuracy understand the Quranic text first arrangement between these processes an average of (1.33) and a standard deviation of (0.80), while knowledge of the different ways to understand the text in the final rankings with an average process amounted to (0.75) and a standard deviation of (0.87) came , then the researcher built imagine a proposal for the development of these processes , and the study recommended some of the recommendations , including: the need to include mental processes associated with metacognitive reading comprehension of the Quranic text in the curriculum of the explanation for the students of the first grade secondary , and provide curriculum modern tools to measure reveals these processes, and the training of teachers on learning strategies for modern development of a cognitive reading comprehension associated with the Quranic text.
Keywords: العمليات الذهنية -- تدريس القرآن -- طلاب المدارس الثانوية